UJI pH DAN ORGANOLEPTIK SUSU KAMBING PASTEURISASI DENGAN PENAMBAHAN BIJI CHIA - Kholifah, Nur; Nunur Nuraeni (Nusantara Hasana Journal, 2025)
This study aimed to determine the effect of adding chia seeds (Salvia hispanica L.) on the physical and organoleptic quality of pasteurized goat milk, as well as to identify the optimal concentration that remains acceptable to consumers. The research was conducted in Sumeradi Village, Kebumen District, Kebumen Regency, from May to June 2025. The experimental design used was a Completely Randomized Design (CRD) with four treatments and four replications: P0 (0% chia), P1 (1% chia), P2 (2% chia), and P3 (3% chia). The observed parameters included pH and organoleptic attributes (color, aroma, taste, texture, and overall acceptability). The addition of chia seeds decreased the pH of pasteurized goat milk from 6.675 (P0) to 6.3 (P2 and P3), although the values remained within the neutral range. Organoleptic evaluation indicated a decline in scores for color, aroma, taste, texture, and acceptability as the chia concentration increased. The control treatment (P0) consistently received the highest scores across all sensory parameters. Analysis of variance revealed that while some differences among treatments were not statistically significant (p>0.05), a descriptive trend of sensory quality reduction was observed. Chia seeds have potential as a functional additive in pasteurized goat milk; however, their use should be limited. A 1% chia seed concentration (P1) was identified as the optimal level, as it did not significantly compromise quality and remained acceptable to consumers.